Variations of the antimicrobial, antioxidant, sensory attributes and biogenic amines content in Lithuania-derived bee products. (January 2020) - Bartkiene, Elena; Lele, Vita; Sakiene, Vytaute; Zavistanaviciute, Paulina; Zokaityte, Egle; Dauksiene, Agila; Jagminas, Povilas; Klupsaite, Dovile; Bliznikas, Saulius; Ruzauskas, Modestas
Abstract: This study examined the antimicrobial and antioxidant properties, overall acceptability (OA), including influence of the product-induced emotions, and biogenic amine (BA) content in fourteen honey (H1–14), four propolis (P15–18) and four bee bread (BB19–22) samples, collected in northwest Lithuania. The all tested bacteria were inhibited by summer honey H13. P18 inhibited 10, while bee breads inhibited 10–11 out of the 15 tested bacteria strains. All propolis-samples inhibited B.cereus and P.multocida. The highest antioxidant activity and content of total phenolic compounds (TPC) were found in bee bread (93% and 394 mg GAE/100 g, respectively). The TPC had moderate and strong negative correlations with the L * ( r  = −0.58) and b * colour coordinates ( r  = −0.66), respectively. The each bee products group (BPs) induced different intensities of emotions, and the OA showed a moderate positive correlation with the "neutral" emotion ( r  = 0.47). A low content of BAs (<15 mg/kg) was identified in six honeys, two bee breads and one propolis sample. In sum, Lithuanian bee products possessed valuable biological attributes that can be beneficially used in food industry and medicine, although further research is needed for the factors, which may contribute to bioactive properties of this region bee products and BAs formation. Highlights: All the tested bee products showed antimicrobial activities. The highest content of total phenolic compounds (TPC) was found in polyfloral bee bread. The acceptability of bee products was influenced by the colour and the TPC. The emotional evaluation of bee products with FaceReader was performed. Biogenic amines were identified in six honeys, two bee breads and one propolis.